Problem Solving Ability: Symbolic Level Analysis in Chemistry Education Students on the Topic of Chemical Equilibrium - Aceng Haetami; Elsya Febiana Fahira; La Rudi; Benjamin Laurentino Vaz (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2022)
This study aimed to determine the ability to solve chemical problems at the symbolic level of chemistry education students and to determine student responses to the Three Tier test question model. The method used descriptive. The sample this study were chemistry education students at Halu Oleo University with totalling 73 students. Data collection in this study was carried out using research instruments in the form of Three Tier Test questions and student response questionnaires to the question model. The analysis results show that 16.3% of students understand the concept, 60.3% have misconceptions, and 23.4% do not understand the concept.